Magnetic relaxation induced by transverse flux shaking in MgB2 superconductors - Nieva, Gladys; Luzuriaga, J.; Badía-Majós, A.; Nieva, G.; Giordano, J.L.; Lopez, C.; Serquis, A.; Serrano, G. (IOP Publishing, 2009)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina